Security behaviors of smartphone users. (14th March 2016) - Das, Amit; Khan, Habib Ullah
Abstract : Purpose: – This paper aims to report on the information security behaviors of smartphone users in an affluent economy of the Middle East. Design/methodology/approach: – A model based on prior research, synthesized from a thorough literature review, is tested using survey data from 500 smartphone users representing three major mobile operating systems. Findings: – The overall level of security behaviors is low. Regression coefficients indicate that the efficacy of security measures and the cost of adopting them are the main factors influencing smartphone security behaviors. At present, smartphone users are more worried about malware and data leakage than targeted information theft. Research limitations/implications: – Threats and counter-measures co-evolve over time, and our findings, which describe the state of smartphone security at the current time, will need to be updated in the future. Practical implications: – Measures to improve security practices of smartphone users are needed urgently. The findings indicate that such measures should be broadly effective and relatively costless for users to implement. Social implications: – Personal smartphones are joining enterprise networks through the acceptance of Bring-Your-Own-Device computing. Users' laxity about smartphone security thus puts organizations at risk. Originality/value: – The paper highlights the key factors influencing smartphone security and compares the situation for the three leading operating systems in the smartphone market.